Lexicography, or the Gentle Art of Making Mistakes (Altre Modernità, 2017)
The man in the street’s attitude of mind towards dictionaries is that they are the true repositories of all the words in a language, and that they are both authoritative and objective – in short, dictionaries are perfect. By mainly referring to the early history of English mono- and bilingual lexicography, this essay explodes the myth of the perfect dictionary and shows that mistakes in dictionaries may profitably be discussed under two headings: lexicographical mistakes, i.e. vague or circular definitions and the so-called ghost words in monolingual dictionaries, and non-insertable equivalents in bilingual dictionaries; and socio-cultural mistakes, which are related to the often elusive impact of ideology on dictionary-making.